Genetic variations of the ADIPOQ gene and risk of prostate cancer in Chinese Han men - Gu, Cheng-Yuan (Asian J Androl, 2014)
Adiponectin secreted by adipose tissue has been implicated in prostate carcinogenesis. Genetic variations in ADIPOQ are thought to influence the activity of adiponectin, thus relating to cancer occurrence. In this hospital-based case-control study of 917 prostate cancer (PCa) cases and 1036 cancer-free controls, we evaluated the association of single nucleotide polymorphisms in ADIPOQ with risk of PCa and adiponectin levels in Chinese Han men. Variants of ADIPOQ were genotyped by Taqman polymerase chain reaction method. The plasma adiponectin concentrations were measured by enzyme-linked immunosorbent assay (ELISA) in a subset of cases and controls. We found that the ADIPOQ rs3774262 variant AA genotype was associated with both decreased PCa risk [adjusted odds ratio (OR): 0.66, 95% confidence interval (CI) =0.48–0.92] and increased plasma adiponectin levels (P = 0.036 and 0.043), with significant difference by tumor grade, clinical stage, and aggressiveness. A significant interaction between ADIPOQ rs3774262 and body mass index was observed in modifying the risk of PCa (P = 6.7 × 10(−3)). ADIPOQ rs266729 and rs182052 were not related to PCa risk or plasma adiponectin levels. Our data support that ADIPOQ rs3774262 may affect PCa risk in combination with plasma adiponectin levels in Chinese Han men. It may contribute to the molecular basis for the association between obesity and PCa.